Analysis of the influence of financial literacy on investment decisions of millennials and gen Z in the digital ERA - Nurhayati, Nunung; Mutakin, Kikin; Caroline, Caroline; Judijanto, Loso (Edelweiss Applied Science and Technology, 2025)
In the digital era, the investment landscape has been transformed by the proliferation of online platforms and fintech solutions, creating new opportunities and challenges for younger generations. This study investigates the influence of financial literacy on the investment decisions of Millennials and Gen Z, two cohorts that are increasingly participating in financial markets through digital channels. Using a mixed-methods approach, we combine quantitative analysis from surveys conducted with 600 individuals across these age groups with qualitative insights gathered from in-depth interviews. The results show that financial literacy significantly affects investment behavior, with those possessing higher levels of financial knowledge demonstrating a more strategic approach to portfolio diversification, risk management, and long-term financial planning. Furthermore, the study finds that digital tools and platforms, such as robo-advisors, investment apps, and online trading platforms, play a crucial role in shaping the investment choices of Millennials and Gen Z, especially as they seek accessible, low-cost options for managing their investments. Key factors influencing these investment decisions include risk tolerance, trust in digital platforms, and the impact of social media influencers on financial decision-making. The research highlights the need for targeted financial education programs that can enhance financial literacy, improve investment outcomes, and encourage responsible investing behaviors among younger generations. These findings provide valuable insights for policymakers, financial institutions, and educators aiming to promote sustainable financial habits and improve the overall financial well-being of Millennials and Gen Z in the digital age.